The Impact of VAAs on Vote Switching at the 2019 Belgian Legislative Elections: More Switchers, but Making Their Own Choices - Talukder, David; Uyttendaele, Laura; Jennart, Isaïa; Rihoux, Benoît (Politics of the Low Countries, 2025)
During electoral campaigns, the use of voting advice applications (VAAs) has become increasingly widespread. Consequently, scholars have examined both the patterns of usage and their effects on voting behaviour. However, existing studies lead to conflicting findings. In this article, we take a closer look at the effect of De Stemtest/Test électoral (a VAA developed by academics from the University of Louvain and the University of Antwerp, in partnership with Belgian media partners) on vote switching. More specifically, we divide this latter question into two subquestions: (1) What is the impact of a (dis)confirming advice from the VAA on vote switching? (2) Do VAA users follow the voting advice provided by the VAA? Our study shows that receiving a disconfirming advice from the VAA increases the probability of users to switch their vote choice.